Equazioni Logaritmiche
Equazioni Logaritmiche
Equazioni Logaritmiche
equazioni logaritmiche risolubili mediante definizione ed applicazione dei teoremi sui logaritmi
1 𝑙𝑙𝑙𝑙𝑙𝑙3 𝑥𝑥 = 2 𝑥𝑥 = 9
2 𝑙𝑙𝑙𝑙𝑙𝑙 1 𝑥𝑥 = −3 𝑥𝑥 = 103
10
3 𝑙𝑙𝑙𝑙(𝑥𝑥 + 2) = 0 𝑥𝑥 = −1
1
4 𝑙𝑙𝑙𝑙(𝑥𝑥 + 1) = −2 𝑥𝑥 = −1
𝑒𝑒 2
−1 ± √65
5 𝑙𝑙𝑙𝑙𝑙𝑙2 (𝑥𝑥 + 2𝑥𝑥 2 ) − 𝑙𝑙𝑙𝑙𝑙𝑙3 9 = 1 𝑥𝑥 =
4
19
7 𝑙𝑙𝑙𝑙(𝑥𝑥 − 2) − 𝑙𝑙𝑙𝑙 3 = 𝑙𝑙𝑙𝑙(5 − 𝑥𝑥) − 𝑙𝑙𝑙𝑙 2 𝑥𝑥 =
5
5
8 𝑙𝑙𝑙𝑙(4𝑥𝑥 + 5) + 𝑙𝑙𝑙𝑙(𝑥𝑥 − 2) = 𝑙𝑙𝑙𝑙3 + 𝑙𝑙𝑙𝑙(5 − 𝑥𝑥) 𝑥𝑥 =
2
9
10 𝑙𝑙𝑙𝑙 2 + 𝑙𝑙𝑙𝑙 𝑥𝑥 = 2 𝑙𝑙𝑙𝑙(4𝑥𝑥 − 15) 𝑥𝑥 =
2
𝑥𝑥
11 𝑙𝑙𝑙𝑙2𝑥𝑥 + 𝑙𝑙𝑙𝑙 = 𝑙𝑙𝑙𝑙4 𝑥𝑥 = 2
2
1
12 𝑙𝑙𝑙𝑙𝑙𝑙 = 2𝑙𝑙𝑙𝑙2𝑥𝑥 𝑥𝑥 =
4
−1 ± √17
13 𝑙𝑙𝑙𝑙𝑙𝑙5 (𝑥𝑥 2 + 𝑥𝑥 + 1) = 1 𝑥𝑥 =
2
1
17 𝑙𝑙𝑙𝑙𝑙𝑙𝑥𝑥 2 = 𝑥𝑥 = 2√2
√2
1 1 1
18 𝑙𝑙𝑙𝑙𝑙𝑙3 2 + 𝑙𝑙𝑙𝑙𝑙𝑙3 𝑥𝑥 = 𝑙𝑙𝑙𝑙𝑙𝑙3 + 𝑙𝑙𝑙𝑙𝑙𝑙3 𝑥𝑥 =
2
2 𝑥𝑥
3 ± √5
19 𝑙𝑙𝑙𝑙𝑙𝑙(2𝑥𝑥 + 2) − 𝑙𝑙𝑙𝑙𝑙𝑙(𝑥𝑥 − 1) = 1 − [𝑙𝑙𝑙𝑙𝑙𝑙(3𝑥𝑥 − 2) − 𝑙𝑙𝑙𝑙𝑙𝑙 𝑥𝑥] 𝑥𝑥 =
2
20 𝑙𝑙𝑙𝑙𝑙𝑙3 𝑥𝑥 = 1 𝑥𝑥 = 3
2
21 𝑙𝑙𝑙𝑙𝑙𝑙3 (2𝑥𝑥 − 1) = −1 𝑥𝑥 =
3
3 11
23 𝑙𝑙𝑙𝑙𝑙𝑙4 (3𝑥𝑥 − 4) = − 𝑥𝑥 =
8
2
𝑥𝑥 − 2 10
24 𝑙𝑙𝑙𝑙𝑙𝑙3 = −2 𝑥𝑥 =
2 3 3
25 𝑙𝑙𝑙𝑙𝑙𝑙𝑥𝑥 4 = 1 𝑥𝑥 = 4
27 𝑙𝑙𝑙𝑙𝑙𝑙𝑥𝑥−2 9 = 2 𝑥𝑥 = 5
28 𝑙𝑙𝑙𝑙𝑙𝑙1 −2 = 2 𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖
𝑥𝑥
1 3 − √3
29 𝑙𝑙𝑙𝑙𝑙𝑙3−2𝑥𝑥 = −2 𝑥𝑥 =
3 2
1
31 𝑙𝑙𝑙𝑙𝑙𝑙3 (3𝑥𝑥 + 1) − 𝑙𝑙𝑙𝑙𝑙𝑙3 𝑥𝑥 = 2 𝑥𝑥 =
6
1 2
33 𝑙𝑙𝑙𝑙𝑙𝑙3 𝑥𝑥 2 + 2 = − 𝑙𝑙𝑙𝑙𝑙𝑙1 2 𝑥𝑥 = ±
2 3 9
1
36 2 𝑙𝑙𝑙𝑙𝑙𝑙1 � 𝑥𝑥 − 1� = 2 − 𝑙𝑙𝑙𝑙𝑙𝑙9 𝑥𝑥 4 𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖
3 3
3𝑥𝑥 − 1 1
37 𝑙𝑙𝑙𝑙𝑙𝑙2 𝑙𝑙𝑙𝑙𝑙𝑙3 =2 𝑥𝑥 = −
78
𝑥𝑥
38 𝑙𝑙𝑙𝑙𝑙𝑙1 𝑙𝑙𝑙𝑙𝑙𝑙2 (3𝑥𝑥 − 1) = 0 𝑥𝑥 = 1
3
2
39 𝑙𝑙𝑙𝑙𝑙𝑙2 𝑙𝑙𝑙𝑙(𝑥𝑥 + 1) = 1 − 𝑙𝑙𝑙𝑙𝑙𝑙4 3 𝑥𝑥 = 𝑒𝑒 √3 − 1
41 𝑙𝑙𝑙𝑙𝑙𝑙2 2 𝑥𝑥 − 4 𝑙𝑙𝑙𝑙𝑙𝑙2 𝑥𝑥 + 4 = 0 𝑥𝑥 = 4
5
44 3 𝑙𝑙𝑙𝑙𝑙𝑙2 𝑥𝑥 + 5 𝑙𝑙𝑙𝑙𝑙𝑙 𝑥𝑥 = 0 𝑥𝑥 = 1 ∪ 𝑥𝑥 = 10−3
1
45 𝑙𝑙𝑙𝑙𝑙𝑙32 𝑥𝑥 + 𝑙𝑙𝑙𝑙𝑙𝑙3 𝑥𝑥 − 12 = 0 𝑥𝑥 = 27 𝑥𝑥 =
81
1
46 −2𝑙𝑙𝑙𝑙2 𝑥𝑥 + 𝑙𝑙𝑙𝑙𝑙𝑙 + 1 = 0 𝑥𝑥 = 𝑒𝑒 𝑥𝑥 =
√𝑒𝑒
47 𝑙𝑙𝑙𝑙3 𝑥𝑥 − 9𝑙𝑙𝑙𝑙𝑙𝑙 = 0 𝑥𝑥 = 1 𝑥𝑥 = 𝑒𝑒 3 𝑥𝑥 = 𝑒𝑒 −3
48 𝑙𝑙𝑙𝑙2 𝑥𝑥 − 2 𝑙𝑙𝑙𝑙 𝑥𝑥 + 1 = 0 𝑥𝑥 = 𝑒𝑒
7
49 𝑙𝑙𝑙𝑙𝑙𝑙 𝑥𝑥 (𝑙𝑙𝑙𝑙𝑙𝑙 𝑥𝑥 + 1) + 5 𝑙𝑙𝑙𝑙𝑙𝑙 𝑥𝑥 = 𝑙𝑙𝑙𝑙𝑙𝑙2 𝑥𝑥 + 4 𝑙𝑙𝑙𝑙𝑙𝑙 𝑥𝑥 − 7 𝑥𝑥 = 10−2
2
52 2 𝑙𝑙𝑙𝑙𝑙𝑙2 (𝑥𝑥 + 3) + =5 𝑥𝑥 = √2 − 3 ∪ 𝑥𝑥 = 1
𝑙𝑙𝑙𝑙𝑙𝑙2 (𝑥𝑥 + 3)
1 2
53 + =2 𝑥𝑥 = 10 ∪ 𝑥𝑥 = √10/10
𝑙𝑙𝑙𝑙𝑙𝑙 𝑥𝑥 𝑙𝑙𝑙𝑙𝑙𝑙 𝑥𝑥 + 1
𝑙𝑙𝑙𝑙 𝑥𝑥 + 1
54 =1 𝑥𝑥 = 1 ∪ 𝑥𝑥 = 𝑒𝑒
𝑙𝑙𝑛𝑛2 𝑥𝑥 + 1
55 (𝑙𝑙𝑙𝑙𝑙𝑙 𝑥𝑥 − 3)(𝑙𝑙𝑙𝑙𝑙𝑙 𝑥𝑥 + 3) = 0 𝑥𝑥 = 103 ∪ 𝑥𝑥 = 10−3
56 𝑙𝑙𝑙𝑙𝑙𝑙5 𝑥𝑥 − 𝑙𝑙𝑙𝑙𝑙𝑙25 𝑥𝑥 = 1 𝑥𝑥 = 25
3 3 1 −2√7±2
57 + =− 𝑥𝑥 = 2 √7
𝑙𝑙𝑙𝑙𝑙𝑙4 𝑥𝑥 2 + 𝑙𝑙𝑙𝑙𝑙𝑙4 𝑥𝑥 𝑙𝑙𝑙𝑙𝑙𝑙4 𝑥𝑥 + 1
4 − 2 𝑙𝑙𝑙𝑙𝑙𝑙4 𝑥𝑥 5 + 3 𝑙𝑙𝑙𝑙𝑙𝑙4 𝑥𝑥 4
58 = 𝑥𝑥 = 43
𝑙𝑙𝑙𝑙𝑙𝑙4 𝑥𝑥 3 𝑙𝑙𝑙𝑙𝑙𝑙4 𝑥𝑥 + 5
59 𝑙𝑙𝑙𝑙𝑙𝑙22 𝑥𝑥 − 4 𝑙𝑙𝑙𝑙𝑙𝑙2 𝑥𝑥 + 3 = 0 𝑥𝑥 = 2 ∪ 𝑥𝑥 = 8
5
61 𝑙𝑙𝑙𝑙𝑙𝑙32 (𝑥𝑥 + 2) − 𝑙𝑙𝑙𝑙𝑙𝑙3 (𝑥𝑥 + 2) − 2 = 0 𝑥𝑥 = − ∪ 𝑥𝑥 = 7
3
62 3𝑙𝑙𝑙𝑙𝑙𝑙12 𝑥𝑥 − 11𝑙𝑙𝑙𝑙𝑙𝑙1 𝑥𝑥 − 4 = 0 3
𝑥𝑥 = √2 𝑥𝑥 =
1
2 2 16
64 𝑙𝑙𝑙𝑙𝑙𝑙22 𝑥𝑥 − 𝑙𝑙𝑙𝑙𝑙𝑙2 𝑥𝑥 3 + 2 = 0 𝑥𝑥 = 2 ∪ 𝑥𝑥 = 4
2 4
67 𝑙𝑙𝑙𝑙𝑙𝑙𝑥𝑥−1 3 − 𝑙𝑙𝑙𝑙𝑙𝑙𝑥𝑥−1 3 − 2 = 0 𝑥𝑥 = ∪ 𝑥𝑥 = 1 + √3
3
5 7
𝑥𝑥 = ∪ 𝑥𝑥 =
2 2
68 𝑙𝑙𝑙𝑙𝑙𝑙24 (2𝑥𝑥 − 3) − 5𝑙𝑙𝑙𝑙𝑙𝑙22 (2𝑥𝑥 − 3) + 4 = 0 7 13
∪ 𝑥𝑥 = ∪ 𝑥𝑥 =
4 8
𝑥𝑥 = −1 ∪ 𝑥𝑥 = 2
69 2𝑙𝑙𝑙𝑙𝑙𝑙42 𝑥𝑥(𝑥𝑥 − 1) + 𝑙𝑙𝑙𝑙𝑙𝑙1 [𝑥𝑥(𝑥𝑥 − 1)]7 + 3 = 0 1 ± √257
4 ∪ 𝑥𝑥 =
2
√3 − 9
70 2
𝑙𝑙𝑙𝑙𝑙𝑙2𝑥𝑥+1 27 + 𝑙𝑙𝑙𝑙𝑙𝑙2𝑥𝑥+1 1�27 − 6 = 0 𝑥𝑥 = 1 ∪ 𝑥𝑥 =
18
𝑥𝑥 = −2 ± √5
75 𝑙𝑙𝑙𝑙𝑙𝑙12 [𝑥𝑥(𝑥𝑥 + 4)] = 𝑙𝑙𝑙𝑙𝑙𝑙1 [𝑥𝑥(𝑥𝑥 + 4)]
2 4 ± 3√2
2 ∪ 𝑥𝑥 = −
2
27
𝑥𝑥 = ±�
2
76 𝑙𝑙𝑙𝑙𝑙𝑙3 2𝑥𝑥 2 (𝑙𝑙𝑙𝑙𝑙𝑙3 2𝑥𝑥 2 − 1) = 𝑙𝑙𝑙𝑙𝑙𝑙3 2𝑥𝑥 2 + 3
1
∪ 𝑥𝑥 = ±�
6
1
77 𝑙𝑙𝑙𝑙𝑙𝑙2 (𝑥𝑥 − 3)2 (𝑙𝑙𝑙𝑙𝑙𝑙2 (𝑥𝑥 − 3) − 2) − 𝑙𝑙𝑙𝑙𝑙𝑙1 (𝑥𝑥 − 3) = 2 𝑥𝑥 = 7 ∪ 𝑥𝑥 = +3
2 √2
3
𝑥𝑥 = −1 ∪ 𝑥𝑥 =
2
78 𝑙𝑙𝑙𝑙𝑙𝑙32 (2𝑥𝑥 2 − 𝑥𝑥) = 1
3 ± √33
∪ 𝑥𝑥 =
12
79 𝑙𝑙𝑙𝑙 2𝑥𝑥 = 0 𝑥𝑥 = 0
1 1
81 𝑙𝑙𝑙𝑙𝑙𝑙5 2𝑥𝑥 −1 = 𝑥𝑥 = 1 +
4 𝑙𝑙𝑙𝑙𝑙𝑙5 2
4
82 𝑙𝑙𝑙𝑙(1 − 𝑒𝑒 𝑥𝑥 ) = 0 𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖
𝑙𝑙𝑙𝑙 10
83 1 − 𝑙𝑙𝑙𝑙𝑙𝑙 3𝑥𝑥 = 𝑙𝑙𝑙𝑙𝑙𝑙 2𝑥𝑥 𝑥𝑥 =
𝑙𝑙𝑙𝑙 6
1
84 𝑙𝑙𝑙𝑙𝑙𝑙(3𝑥𝑥 + 1) + 𝑙𝑙𝑙𝑙𝑙𝑙(3𝑥𝑥 − 1) = 2 𝑥𝑥 = 𝑙𝑙𝑙𝑙𝑙𝑙3 101
2
𝑙𝑙𝑙𝑙 5
85 𝑥𝑥 𝑙𝑙𝑙𝑙𝑙𝑙2 3 + 𝑙𝑙𝑙𝑙𝑙𝑙2 5𝑥𝑥 = (2𝑥𝑥 − 1) 𝑙𝑙𝑙𝑙𝑙𝑙2 5 − 𝑥𝑥 𝑙𝑙𝑙𝑙𝑙𝑙2 5 𝑥𝑥 = −
𝑙𝑙𝑙𝑙 3
𝑙𝑙𝑙𝑙 5
86 𝑙𝑙𝑙𝑙(22𝑥𝑥 − 9 ∙ 2𝑥𝑥 + 21) = 0 𝑥𝑥 = 2 ∪ 𝑥𝑥 =
𝑙𝑙𝑙𝑙 2
2 −6
88 𝑙𝑙𝑙𝑙 4𝑥𝑥 − 𝑙𝑙𝑙𝑙 64 = 0 𝑥𝑥 = ±3
𝑥𝑥 √2
91
𝑙𝑙𝑙𝑙𝑙𝑙(10 − 𝑥𝑥 2 ) − 𝑙𝑙𝑙𝑙𝑙𝑙 8 = 2 𝑙𝑙𝑙𝑙𝑙𝑙 − 2 𝑙𝑙𝑙𝑙𝑙𝑙 𝑥𝑥 = √2
5 5
1 1
92 (𝑙𝑙𝑙𝑙𝑙𝑙2 𝑥𝑥 2 )2 +9 𝑙𝑙𝑙𝑙𝑙𝑙2 𝑥𝑥 + 2 = 0 𝑥𝑥 = , 𝑥𝑥 = 4
4 √2
3 2 √2
94 + =2 𝑥𝑥 = 8, 𝑥𝑥 =
𝑙𝑙𝑙𝑙𝑙𝑙2 𝑥𝑥 − 1 𝑙𝑙𝑙𝑙𝑙𝑙2 𝑥𝑥 + 1 2
𝑙𝑙𝑙𝑙 4
95 𝑙𝑙𝑙𝑙𝑙𝑙2 3𝑥𝑥 − 2 = 0 𝑥𝑥 =
𝑙𝑙𝑙𝑙 3
𝑥𝑥−1 2
97
𝑙𝑙𝑙𝑙 2 2 −1=0 𝑥𝑥 = 1 +
𝑙𝑙𝑙𝑙 2
3 1 1 2
98 𝑙𝑙𝑙𝑙 2𝑥𝑥 +1 − 2 𝑙𝑙𝑙𝑙 = 1 𝑥𝑥 = �
3 𝑙𝑙𝑙𝑙 2
− 7�
2 2
99 −2 𝐿𝐿𝐿𝐿𝐿𝐿 42−𝑥𝑥 + 5 𝐿𝐿𝐿𝐿𝐿𝐿 2𝑥𝑥+1 = 1 𝑥𝑥 = 𝑙𝑙𝑙𝑙𝑙𝑙512 80
𝑙𝑙𝑙𝑙 9 − 1
101 − 𝑙𝑙𝑙𝑙 2𝑥𝑥 + 2 𝑙𝑙𝑙𝑙 3 = 1 − 𝑙𝑙𝑙𝑙 4−𝑥𝑥 𝑥𝑥 =
𝑙𝑙𝑙𝑙 8
1 1 𝑥𝑥
104 (𝑥𝑥 + 1) 𝑙𝑙𝑙𝑙 3 − 𝑙𝑙𝑙𝑙 = 2 𝑙𝑙𝑙𝑙 � � 𝑥𝑥 = −1
9 3
1
105 𝑙𝑙𝑙𝑙 2 + 4 𝑙𝑙𝑙𝑙𝑙𝑙2 𝑒𝑒 = 0 𝑥𝑥 = −ln2 √2
𝑥𝑥
1 2
106 𝑙𝑙𝑙𝑙 3𝑥𝑥 + 2 𝑙𝑙𝑙𝑙𝑙𝑙3𝑥𝑥 𝑒𝑒 − 3 = 0 𝑥𝑥 = ∪ 𝑥𝑥 =
𝑙𝑙𝑙𝑙 3 𝑙𝑙𝑙𝑙 3
𝑙𝑙𝑙𝑙 10
𝑥𝑥 = −
𝑙𝑙𝑙𝑙 2
107 𝑥𝑥𝑥𝑥𝑥𝑥𝑥𝑥 2 − 3 𝑙𝑙𝑙𝑙𝑙𝑙2𝑥𝑥 10 − 2 = 0 𝑙𝑙𝑙𝑙 10
∪ 𝑥𝑥 = 3
𝑙𝑙𝑙𝑙 2
2
108 2 − 3𝑥𝑥 𝑙𝑙𝑙𝑙𝑙𝑙4 3𝑥𝑥 + 2(𝑙𝑙𝑙𝑙𝑙𝑙4 9 − 𝑙𝑙𝑙𝑙𝑙𝑙4 4) = 0 𝑥𝑥 = ± √3
3
1
109 �(𝑥𝑥 + 1) 𝐿𝐿𝐿𝐿𝐿𝐿 3 − 1�(1 + 𝐿𝐿𝐿𝐿𝐿𝐿 3𝑥𝑥 +1 ) = 0 𝑥𝑥 = −1 ±
𝐿𝐿𝐿𝐿𝐿𝐿 3
4
110 𝐿𝐿𝐿𝐿𝐿𝐿(24𝑥𝑥 − 1) + 2 𝐿𝐿𝐿𝐿𝐿𝐿 3 = (1 − 2𝑥𝑥) 𝐿𝐿𝐿𝐿𝐿𝐿 4 𝑥𝑥 = 𝑙𝑙𝑙𝑙𝑙𝑙16 � �
3
𝑙𝑙𝑙𝑙 24
111 3 − 𝑥𝑥 + 𝑙𝑙𝑙𝑙𝑙𝑙2 32𝑥𝑥+1 = 0 𝑥𝑥 = −
𝑙𝑙𝑙𝑙 9 − 𝑙𝑙𝑙𝑙 2
3
112 𝑙𝑙𝑙𝑙𝑙𝑙3 �9𝑥𝑥+2 − 2� = 𝑥𝑥 + 1 𝑥𝑥 = −1
√5 − 1
113 𝑙𝑙𝑙𝑙|3𝑥𝑥 − 1| = 𝑥𝑥𝑥𝑥𝑥𝑥 9 𝑥𝑥 = 𝑙𝑙𝑙𝑙𝑙𝑙3 � �
2
7
115 𝑙𝑙𝑙𝑙𝑙𝑙 5 − 𝑙𝑙𝑙𝑙𝑙𝑙(2𝑥𝑥 − 3) = 1 𝑥𝑥 =
4
1 3 1 1
119 + 2 = 𝑥𝑥 = ∪ 𝑥𝑥 = 32
2 𝑙𝑙𝑙𝑙𝑙𝑙2 𝑥𝑥 − 2 𝑙𝑙𝑙𝑙𝑙𝑙2 𝑥𝑥 − 1 4 8
𝑙𝑙𝑙𝑙𝑙𝑙 𝑥𝑥 − 2 𝑙𝑙𝑙𝑙𝑙𝑙 𝑥𝑥 − 2 𝑙𝑙𝑙𝑙𝑙𝑙2 𝑥𝑥 − 4 2
120 + = 𝑥𝑥 = 102 ∪ 𝑥𝑥 = 103
𝑙𝑙𝑙𝑙𝑙𝑙 𝑥𝑥 − 1 𝑙𝑙𝑙𝑙𝑙𝑙 𝑥𝑥 − 3 (𝑙𝑙𝑙𝑙𝑙𝑙 𝑥𝑥 − 3)(1 − 𝑙𝑙𝑙𝑙𝑙𝑙 𝑥𝑥)
1 1
127 𝑙𝑙𝑙𝑙(𝑥𝑥 − 1) + 𝑙𝑙𝑙𝑙 √3 = [𝑙𝑙𝑙𝑙(5𝑥𝑥 2 − 20) − 𝑙𝑙𝑙𝑙(𝑥𝑥 − 2)] 𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖𝑖
2 2
128 𝑙𝑙𝑙𝑙𝑙𝑙�51+√𝑥𝑥 + 51−√𝑥𝑥 � = 1 𝑥𝑥 = 0
√3 𝜋𝜋
131 𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐 𝑥𝑥 = 1 ∪ 𝑥𝑥 = ± + 2𝑘𝑘𝑘𝑘
𝑥𝑥 = 𝑥𝑥 2 6
132 𝑥𝑥 𝑥𝑥 = 1 𝑥𝑥 = 1
133 𝑙𝑙𝑙𝑙𝑙𝑙𝑥𝑥 𝑥𝑥 = 0 𝑥𝑥 = 1
3
134 𝑥𝑥 𝑥𝑥 = 𝑥𝑥 3−𝑥𝑥 𝑥𝑥 = ∪ 𝑥𝑥 = 1
2
1
136 𝑥𝑥𝑥𝑥𝑥𝑥𝑥𝑥 3 = 1 𝑥𝑥 =
𝑙𝑙𝑙𝑙 3